LDS1-produced oxylipins are negative regulators of growth, conidiation and fumonisin synthesis in the fungal maize pathogen Fusarium verticillioides - Scala, Valeria; Giorni, Paola; Cirlini, Martina; Ludovici, Matteo; Visentin, Ivan; Cardinale, Francesca; Fabbri, Anna A.; Fanelli, Corrado; Reverberi, Massimo; Battilani, Paola; Galaverna, Gianni; Dall'Asta, Chiara (Frontiers in Microbiology, 2014)
Oxylipins are fatty acid-derived signaling compounds produced by all eukaryotes so far investigated; in mycotoxigenic fungi, they modulate toxin production and interactions with the host plants. Among the many enzymes responsible for oxylipin generation, Linoleate Diol Synthase 1 (LDS1) produces mainly 8-hydroperoxyoctadecenoic acid and subsequently different di-hydroxyoctadecenoic acids. In this study, we inactivated a copy of the putative LDS1 ortholog (acc. N. FVEG_09294.3) of Fusarium verticillioides, with the aim to investigate its influence on the oxylipin profile of the fungus, on its development, secondary metabolism and virulence. LC-MS/MS oxylipin profiling carried out on the selected mutant strain revealed significant quali-quantitative differences for several oxylipins when compared to the WT strain. The Fvlds1-deleted mutant grew better, produced more conidia, synthesized more fumonisins and infected maize cobs faster than the WT strain. We hypothesize that oxylipins may act as regulators of gene expression in the toxigenic plant pathogen F. verticillioides, in turn causing notable changes in its phenotype. These changes could relate to the ability of oxylipins to re-shape the transcriptional profile of F. verticillioides by inducing chromatin modifications and exerting a direct control on the transcription of secondary metabolism in fungi.